2012
DOI: 10.3102/1076998611422912
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Response Time Distributions for Item Selection in CAT

Abstract: Traditional methods for item selection in computerized adaptive testing only focus on item information without taking into consideration the time required to answer an item. As a result, some examinees may receive a set of items that take a very long time to finish, and information is not accrued as efficiently as possible. The authors propose two item-selection criteria that utilize information from a lognormal model for response times. The first modifies the maximum information criterion to maximize informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
110
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(114 citation statements)
references
References 26 publications
0
110
3
1
Order By: Relevance
“…Equation 6 for the distribution of T j (Fan et al, 2012). Using maximum likelihood to estimate both u and t, Fan et al showed that estimation accuracy only differed slightly between the original maximum information criterion in Equation 15 and that in Equation 17, but that using the latter substantially reduced the average time needed by examinees to complete the test.…”
Section: Using Rt To Modify Item Selection Criteria In Cctmentioning
confidence: 99%
See 4 more Smart Citations
“…Equation 6 for the distribution of T j (Fan et al, 2012). Using maximum likelihood to estimate both u and t, Fan et al showed that estimation accuracy only differed slightly between the original maximum information criterion in Equation 15 and that in Equation 17, but that using the latter substantially reduced the average time needed by examinees to complete the test.…”
Section: Using Rt To Modify Item Selection Criteria In Cctmentioning
confidence: 99%
“…Using maximum likelihood to estimate both u and t, Fan et al showed that estimation accuracy only differed slightly between the original maximum information criterion in Equation 15 and that in Equation 17, but that using the latter substantially reduced the average time needed by examinees to complete the test. For the current study, the ''maximum information per time unit'' framework introduced by Fan et al (2012) is extended to the current context of CCT. It is seen in Equation 17 that the numerator of the item selection criterion is evaluated at an interim ability estimateû kÀ1 , which, for CCT, results in higher ATL than Fisher information at the mastery threshold (Spray & Reckase, 1994).…”
Section: Using Rt To Modify Item Selection Criteria In Cctmentioning
confidence: 99%
See 3 more Smart Citations